2023
DOI: 10.3390/educsci13010063
|View full text |Cite
|
Sign up to set email alerts
|

Digitally Enabled Experiential Learning Spaces for Engineering Education 4.0

Abstract: Novel digital technologies have transformed societies, organizations, and individuals in diverse aspects of daily life, elevating their competency requirements in order to successfully develop, integrate, and generate value. To remain relevant Higher education should provide students with digitally enhanced learning experiences to build their necessary competencies. To progress in this direction, this work proposes a method that can be used to develop digitally enabled experiential learning spaces (DeELS) in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Referring to the methods of assessment, students obtained a higher mean and median mark in the project than in the exam, with a smaller standard deviation and interquartile range (IQR). These results are consistent with previous work with experiential learning experiences [40,60].…”
supporting
confidence: 93%
“…Referring to the methods of assessment, students obtained a higher mean and median mark in the project than in the exam, with a smaller standard deviation and interquartile range (IQR). These results are consistent with previous work with experiential learning experiences [40,60].…”
supporting
confidence: 93%
“…In 2017, the online plattform "GOAL Project" was created to support undergraduate students' learning on supply chain management and increase their engagement. This platform contains innovative learning materials, including videos, notes, quizzes, simulators, and games (Pacheco-Velázquez, 2015;Pacheco-Velazquez & Aguilar-Avalo, 2019;Pacheco-Velazquez & Viscarra-Campos, 2019;Salinas-Navarro, Pacheco-Velazquez, Arana-Solares & Palma-Mendoza, 2020;Pacheco & Palma-Mendoza, 2021;Pacheco-Velazquez, 2022). An adapted version of a well-known SDL survey (Fisher et al, 2001) was implemented from 2017 to 2020 across multiple academic terms.…”
Section: Introductionmentioning
confidence: 99%
“…Today, in the era of digitalization of information, it is appreciated that university students tend to read and write less due to the use of digital platforms with videos where they learn new topics through tutorials or virtual classes [7,8]. University students rarely go to the library to look for printed books, but rather prefer to use digital books, for example.…”
Section: Introduction 1the Reality Faced By Undergraduate Engineering...mentioning
confidence: 99%
“…These studies are available in scientific databases as scientific articles and can be found in: Scopus, Web of Science, Science Direct, IEEE, Dialnet, ProQuest, EBSCO, Springer, Nature, MDPI, Scielo, among others. Another alternative to obtaining information to develop research by students is to access repositories from different universities and download undergraduate and graduate theses[8].…”
mentioning
confidence: 99%